Cindy Sherman, "Centerfold (Untitled #96)" - Allen, Gwen 1971- (The Museum of Modern Art, 2021)
"In 1981 Cindy Sherman (born 1954) was commissioned to contribute a special project to Artforum magazine. Given two facing pages, she chose to explore the pornographic centerfold, creating 12 large-scale horizontal images of herself appearing as various young women, often reclining, in private, melancholic moments of reverie. As Sherman explained, 'I wanted a man opening up the magazine to suddenly look at it in expectation of something lascivious and then feel like the violator that they would be.' Sherman's Centerfolds were so provocative that they were never published for fear that they would be misunderstood. In her essay, Gwen Allen, Professor of Art History and Director of the School of Art at San Francisco State University, examines one of the most iconic photographs in the series, Untitled #96--in which a young woman lies on her back against an orange and yellow vinyl floor, clutching a scrap of newspaper--exploring the production and critical reception of Sherman's Centerfolds in relationship to the politics of pornography, gender and representation."--Brookline Booksmith (viewed on February 17, 2021)
Keywords: Sherman, Cindy -- 1954-; Sherman, Cindy / Untitled #96; Museum of Modern Art (New York, N.Y.)